The Development of Illustrated Science Student Worksheets with Scientific Approach to Improve Questioning Skills and Learning Outcomes of Elementary Students Regarding Weather Theme and Its Effect on Humans - Joanita Margiandini; Suratno Suratno; Suparti Suparti (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2022)
Elementary school often applies a scientific approach to train students to discover the science phenomena. This research was intended to analyze the process, results and effectiveness after applying the illustrated science student worksheets with scientific approach concerning the weather theme and its effects on humans. The design used in this research was descriptive quantitative and done by 38 students of third grade at SDN Patrang 02 Jember Regency. The analysis of the scientific approach emphasized on research and development, quantitative and descriptive qualitative statistical data analysis. Descriptive qualitative data analysis was taken from interviews with students and questionnaires as well as the pictures of students’ works. It was obtained from the results of interviews, questionnaires and students’ work results. This test covered a large group class of 10 students and a small group class of 28 students. This research involved a large class design of 28 students and a small class of 10 students. The research instruments used were questionnaire, interview, observation, pre-test and post-test. The research analysis was tested for its validity, practicality, effectiveness, normality, homogeneity, and t-test. The results showed that the illustrated science student worksheets with scientific approach developed were valid, practical and effective. According to the analysis on the results of pre-test and post-test in a small class (10 students), there was an increase in the percentage from 58.08% to 83.3%. The analysis on the results of the pre-test post-test in a large class (28 students) got an increase from 54.44% to 88.7%. It claimed that the results of pre-test and post-test developed in the illustrated science student worksheets with scientific approach in both small and large classes improved the students’ questioning skills and learning outcomes during their learning in weather theme and its effects on humans at SDN Patrang 02 Jember